Nilai Motivasi dalam Novel Negeri 5 Menara Karya Ahmad Fuadi: Tinjauan Psikologi Sastra dan Implementasinya Sebagai Bahan Ajar Sastra di SMK Muhammadiyah Kartasura - Meyreni, Anita, Drs. Adyana Sunanda, M.Pd (2017)
The aims of this research are to (1) Describe the structure of the Negeri 5 Menara novel by Ahmad Fuadi, (2) Describe motivation value in Negeri 5 Menaranovel by Ahmad Fuadi, (3) Implementation teaching material of leterature at SMK Muhammadiyah Kartasura by curriculum syllabus. The research method uses descriptive qualitative. This research data is sentences and paragraphs that have motivation value, while the source data is a novel Negeri 5. Technique for collecting data use book technique and field note. Then, technique for analyzing data uses heuristic and hermenutic. The result of this study indicate (1) The structure of the Negeri 5 Menara novel by Ahmad Fuadi is spirit and struggle. The plot is flow fort. (2) Motivation value in Negeri 5 Menara there are motivation external and motivation internal. Motivation external is motivation arising from motives of others. Motivation internal is motivation grew out of yourself. (3) Implementation teaching material of literature at SMK Muhammadiyah Kartasura especially for XII class which refer to KD. 3.1 Understanding structure and text rules historical stories, news, advertisement, editorial/opinion, and fiction in a novel both orally and in writing. As well as trough KD 4.1 interpret the meaning of the tex narrative history, news, advertisement, editorial/opinion, and fiction in a novel both orally and in writing. Keyword: Motivation Value, Psychology of Literature, Negeri 5 Menara.